Computer-assisted design model to evaluate the outcome of combined osteotomies in Legg-Calvé-Perthes disease - Li, Hao; Zhang, Zhiqiang; Li, Changyou; Liang, Zhenpeng; Liu, Zhu; Li, Hai; Zhang, Ziming (Frontiers in Pediatrics, 2022)
Objective The current study aims to conduct a quantitative dynamic analysis of hip morphology using a computer-assisted design (CAD) model to evaluate the combined pelvic and femoral osteotomies in the treatment of Legg-Calvé-Perthes disease (LCPD). Materials and methods CAD models of patients with unilateral LCPD treated by combined pelvic and proximal femoral osteotomies were established based on the data of CT scan, on which morphological parameters were measured. Shape difference analysis of normal hips was adopted to locate the most apparent displacement and the main strain on the surface of the proximal femur. Results Fifteen patients were included, and the mean age of receiving operation was 6.63 years old. There were 10 hips rated as Herring type C, and the rest were type B. Compared with the normal side, the affected hip joints have a longer distance between femoral head and acetabular sphere. The difference of coverage area of the femoral head surface and femoral head volume between the affected and normal sides was bigger compared with the preoperative model, respectively. The changes in the acetabular radius and the area of the surface were not apparent, pre-, and post-operatively. The displacement was mainly on superior and lateral superior portions of the femoral head where the stresses were concentrated. Conclusion Combined pelvic and femoral osteotomies could effectively improve the superior and superior–posterior area of acetabulum containment with increased femoral head volume. CAD model and shape difference analysis can provide a better understanding of deformations of LCPD and more information for surgical planning and evaluation of treatment outcomes.